2000
DOI: 10.1091/mbc.11.11.3897
|View full text |Cite
|
Sign up to set email alerts
|

High Cell Sensitivity toHelicobacter pyloriVacA Toxin Depends on a GPI-anchored Protein and is not Blocked by Inhibition of the Clathrin-mediated Pathway of Endocytosis

Abstract: Helicobacter pylori vacuolating toxin (VacA) causes vacuolation in a variety of cultured cell lines, sensitivity to VacA differing greatly, however, among the different cell types. We found that the high sensitivity of HEp-2 cells to VacA was impaired by treating the cells with phosphatidylinositol-specific phospholipase C (PI-PLC) which removes glycosylphosphatidylinositol (GPI)-anchored proteins from the cell surface. Incubation of cells with a cholesterol-sequestering agent, that impairs both structure and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
170
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(182 citation statements)
references
References 78 publications
12
170
0
Order By: Relevance
“…The subsequent intracellular route is dependent on the cell type, and lipid composition of lipid rafts seems crucial for sorting of intracellular trafficking. Certain bacterial toxins which are active intracellularly, such as Helicobacter pylori VacA (vacuolating toxin) (Ricci et al, 2000) and clostridial NTs (see below), recognize either GPI-anchored proteins or other molecules, but are associated with GPI-anchored proteins as receptors, and enter a specific intracellular pathway. In addition, toxins interacting with GPI-anchored proteins on the cell surface, such as aerolysin, have been used as tools to monitor the sorting of endocytic routes (Fivaz et al, 2002).…”
Section: Endocytic Pathway and Gpi (Glycosylphosphatidylinositol)-ancmentioning
confidence: 99%
“…The subsequent intracellular route is dependent on the cell type, and lipid composition of lipid rafts seems crucial for sorting of intracellular trafficking. Certain bacterial toxins which are active intracellularly, such as Helicobacter pylori VacA (vacuolating toxin) (Ricci et al, 2000) and clostridial NTs (see below), recognize either GPI-anchored proteins or other molecules, but are associated with GPI-anchored proteins as receptors, and enter a specific intracellular pathway. In addition, toxins interacting with GPI-anchored proteins on the cell surface, such as aerolysin, have been used as tools to monitor the sorting of endocytic routes (Fivaz et al, 2002).…”
Section: Endocytic Pathway and Gpi (Glycosylphosphatidylinositol)-ancmentioning
confidence: 99%
“…In a variety of mammalian cell types (Skretting et al, 1999;Ricci et al, 2000;Fivaz et al, 2002) and in Drosophila hemocytes (Guha et al, 2003), GPI-anchored proteins continue to be internalized even when dynamin activity is inhibited. GPI-anchored proteins are then delivered to Rab5-negative GEECs.…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of lateral associations of the type described above, or cross-linking and internalization through the caveolar/raft-dependent pathway (Nabi and Le, 2003), GPI-anchored proteins seem to be selectively internalized through a dynamin-independent pathway (Fivaz et al, 2002;Sabharanjak et al, 2002;Guha et al, 2003). It has been recently shown that the nanoscale organization of GPI-anchored proteins on the plasma membrane also influences their endocytic pathways (Sharma et al, 2004).In a variety of mammalian cell types (Skretting et al, 1999;Ricci et al, 2000;Fivaz et al, 2002) and in Drosophila hemocytes (Guha et al, 2003), GPI-anchored proteins continue to be internalized even when dynamin activity is inhibited. GPI-anchored proteins are then delivered to Rab5-negative GEECs.…”
mentioning
confidence: 99%
“…Intracellular expression of VacA by transient tranfection with VacA-encoding plasmids results in the formation of intracellular vacuoles that are indistinguishable from those that form when VacA is added to the outside of cells (29,30), suggesting that this toxin acts intracellularly. HEp-2 cells expressing dominant negative mutants of two proteins required for clathrin-dependent endocytosis (Eps 15 and dynamin II) develop cellular vacuoles in response to VacA (31), which suggests that VacA internalization can occur via a clathrin-independent endocytic pathway. It has been proposed that VacA toxicity requires localization of the toxin in either endosomes or mitochondria (28,32).…”
mentioning
confidence: 99%
“…In addition, certain bacterial toxins, including aerolysin, perfringolysin O, cholera toxin, and tetanus toxin, utilize rafts as either a site for high affinity binding and oligomerization on the surface of cells or as a site for internalization into host cells (42)(43)(44)(45)(46). A recent study reported that treatment of HEp-2 cells with phosphatidylinositol-specific phospholipase C (PI-PLC), an agent that removes GPIanchored proteins from the cell surface, inhibited the capacity of VacA to induce cell vacuolation (31). It also was reported that incubation of the cells with nystatin (a cholesterol-binding agent) inhibited VacA-induced cell vacuolation (31).…”
mentioning
confidence: 99%